PENGARUH MOTIVASI KERJA, DISIPLIN KERJA DAN BEBAN KERJA TERHADAP KINERJA PEGAWAI HARIAN LEPAS MELALUI KEPUASAN KERJA SEBAGAI VARIABEL INTERVENING PADA POLRES SITUBONDO - Chandra, Venia Avery Dwi; Sari, Lita Permata; Pramesthi, Riska Ayu (Fakultas Ekonomi dan Bisnis, 2024)
The aim of this study is to find out the impact of work motivation, work discipline and workload on the performance of post-day officers through job satisfaction as an intervening variable on Situbondo POLRES. The population on this study is the Officer of the Post-POLRES Situbondo Daily. Simple probability sampling is a method of sample-taking without considering the population in this study. Data analysis and hypothesis testing in research using Structural-partial equation model Least square (PLS-SEM). The results of the hypothesis test of its direct influence using the smart PLS3.2.8 application, show that work motivation has a significant positive effect on job satisfaction, work discipline has a significant positive effect on job satisfaction, workload has a positive but not significant effect on job satisfaction, work motivation has a significant positive effect on performance, work discipline has a significant positive effect on performance, workload has a positive but not significant effect on performance, job satisfaction has a positive but not significant effect on performance, work motivation has a positive but not significant effect on performance through job satisfaction, work discipline has a positive but not significant effect on performance through job satisfaction, workload has a positive but not significant effect on performance through job satisfaction.